Effects of polystyrene nanoplastics and copper on gill tissue structure, metabolism, and immune function of the Chinese mitten crab (Eriocheir sinensis) - Xu, Jian; Feng, Guangpeng; Yan, Yunzhi (Frontiers in Marine Science, 2025)
Nanoplastics (NPs) and copper (Cu) are increasingly released into aquatic environments, posing significant risks to aquatic organisms, including crabs. As the primary interface between the organism and the surrounding environment, gills are particularly susceptible to the impacts of NPs and Cu exposure. Investigating the toxicity of these pollutants, especially their combined effects, is crucial for assessing their environmental risks. This study evaluated the toxicity of NPs (0.4 mg/L), Cu²+ (0.1 mg/L), and the combination (NPs + Cu²+) on the gill tissues of Eriocheir sinensis, focusing on tissue morphology, metabolism, and immune functions. The results demonstrated that exposure to NPs, Cu²+ and NPs + Cu²+ caused structural damage to gill tissues and significantly elevated antioxidant parameters such as GSH-Px activity and GSH content, as well as immune parameters including ACP and AKP activity. Compared with the single exposure group, energy metabolism-related genes (TAT, TPI, HK) were down-regulated in the combined exposure group. Pathways associated with glutathione metabolism and cytochrome P450 were notably affected, and the combined exposure suppressed the expression of immune-related genes such as CYP450, GST, and UGT. In summary, we found an enhanced toxicological impact of NPs when combined with Cu2+. Thus, this study provides insights into the toxicological mechanisms of NPs and Cu²+ in aquatic organisms, highlighting their ecological risks to aquatic ecosystems.